Revocation for Delegatable Anonymous Credentials - Acar, Tolga; Nguyen, Lan (2010)
This paper introduces and formalizes homomorphic proofs that allow `adding' proofs and proof statements to get a new proof of the `sum' statement. Additionally, we introduce a construction of homomorphic proofs, and show an accumulator scheme with delegatable non-membership proofs (ADNMP) as one of its applications with provable security. Finally, the proposed accumulator method extends the BCCKLS scheme to create a new provably secure revocable delegatable anonymous credential (RDAC) system. Intuitively, the new accumulator's delegatable non-membership (NM) proofs enable user A, without revealing her identity, to delegate to user B the ability to prove that A's identity is not included in a blacklist that can later be updated. The delegation is redelegatable, unlinkable, and verifiable.
International Association for Cryptologic Research